Scapular dyskinesis in patients with breast cancer (Annals of Medical Research, 2021)
Aim: To determine the incidence of scapular dyskinesis in breast cancer patients, to compare it with controls, and to investigate the triggering factors, analyzing restriction, pain and function of the shoulder, lymphedema, time after surgery, radiotherapy, chemotherapy, number of removed lymph nodes. Scapular dyskinesis is one of the complications after breast cancer treatment, without a consensual incidence ratio. Only a few studies in literature mention the incidence of scapula alata which is advanced form of scapular dyskinesis in patients with breast cancer, most of which insufficiently assess the required parameters and with discordant results. Material and Methods: The study sample comprised forty-nine patients who had undergone axillar dissection and forty-nine healthy individuals as controls. Scapular dyskinesis, shoulder mobility, pain, lymphedema and function of shoulder were evaluated with lateral scapular slide test, goniometer, visual analogue scale, circumference measurement and Disabilities of the Arm, Shoulder and Hand Questionnaire, respectively. Results: The incidence of scapular dyskinesis was 53.06 % in patients with breast cancer and significantly higher than the control group (p= 0.007). None of the parameters investigated have a significant relationship with scapular dyskinesis statistically (p>0.05).Conclusion: The results indicate that the incidence of scapular dyskinesis is significantly higher in breast cancer therefore it will be beneficial that scapular dyskinesis is included in and thoroughly scrutinized during the clinical assessments; and medical practitioners dealing with breast cancer patients are informed of a potential scapular dyskinesis should need be.
Keywords: Axillar dissection; breast cancer; scapular dyskinesis; winged scapula